Terapi Nonfarmakologis Dismenorea: Kombinasi Kompres Hangat dan Relaksasi Napas Dalam - Siregar, Eka Darmayanti Putri; Salsabilla Firda Hartanto; Susanti; Yeti Mareta Undaryati (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Adolescence refers to individuals aged 10 to 19 years, a stage distinguished by physical, hormonal, social, and psychological changes collectively known as the signs of puberty. One of the common pubertal signs in adolescent girls is menstruation, which in some cases is accompanied by anxiety due to pain, known as dysmenorrhea. Dysmenorrhea can be managed through both pharmacological and non-pharmacological approaches. Among the non-pharmacological methods, warm compresses and deep breathing relaxation techniques are considered effective, easily applied, and affordable options for pain management. This case study intends to present Adolescent midwifery care was provided to Miss A using a combination of warm compress and deep breathing relaxation to alleviate dysmenorrhea, conducted in the Mamburungan Public Health Center area. The case involved an adolescent experiencing dysmenorrhea, who underwent the intervention six times over three days during her menstrual period. The findings revealed a notable decrease in the intensity of dysmenorrhea, shifting from moderate to mild after the applied treatment. The combination this nonpharmacological treatment was shown to be effective in decreasing the severity of dysmenorrhea and is recommended as a non-pharmacological alternative that adolescents may adopt. Keywords: Dysmenorrhea, Warm Compress, Deep Breathing Relaxation